Intensifying homestead climate-smart agriculture and the challenges to its wider adoption in Azuari watershed, Northwest Ethiopia - Debie, Ermias (Frontiers in Sustainable Food Systems, 2024)
The adoption of climate-smart agriculture practices (CSAPs) at the plot level is a promising yet underutilized strategy in Ethiopia, where subsistence farming predominates. This study investigates the factors influencing the intensity of CSAPs on homesteads and identifies key barriers to their broader adoption. The findings reveal that slope gradient, extension contacts, farming experience, dependency ratio-induced labor, and livestock diversity significantly impact farmers' decisions to enhance CSAPs. Major obstacles include insecure land tenure, poor management of open grazing, labor-intensive practices, and limited access to agricultural inputs. These variables should be prioritized in agricultural extension policies to promote the widespread implementation of CSAPs.